Verbal Noun in the Holy Quran - Mohamad Yusuf Ahmad Hasyim (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2014)
Arabic has many characteristics that are not shared by other language in this world. The verbal noun (ism fiʻl) is one among some words that is able to replace the position and the meaning of verbal (fiʻl). Nevertheless they are different in giving the meaning, in te sense that the verbal noun is more compact and more firm. In the holy Al-Qur'an Al-Karim there are approximately twelve verbal nouns. Each has a distinctive role in forming a meaning which is to deal with in this article.